The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnano.2021.679358
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Silver Nanoparticles Against Fungal Pathogens

Abstract: The use of silver nanoparticles (AgNPs) against various pathogens is now being well recognized in the agriculture and health sector. Nanoparticles have been shown to exhibit various novel properties and these properties, on other hand, rely upon the size, shape, and morphology of these particles. Moreover, these physical characteristics enable them to interact with microbes, plants, and animals. Smaller-sized particles have shown more toxicity than larger-sized nanoparticles. AgNPs have shown growth inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 127 publications
1
38
0
2
Order By: Relevance
“…The AgNPs fabricated using Kleinia grandiflora leaf extract at the concentration of 200 µg/mL showed considerable antimicrobial activity against Pseudomonas aeruginosa and Aspergillus niger [ 59 ]. Furthermore, Mansoor, et al [ 60 ] reported that AgNPs inhibited the growth of various fungi, including Aspergillus fumigates, Aspergillus niger, Aspergillus flavus, Trichophyton rubrum, Candida albicans, and Penicillium species.…”
Section: Resultsmentioning
confidence: 99%
“…The AgNPs fabricated using Kleinia grandiflora leaf extract at the concentration of 200 µg/mL showed considerable antimicrobial activity against Pseudomonas aeruginosa and Aspergillus niger [ 59 ]. Furthermore, Mansoor, et al [ 60 ] reported that AgNPs inhibited the growth of various fungi, including Aspergillus fumigates, Aspergillus niger, Aspergillus flavus, Trichophyton rubrum, Candida albicans, and Penicillium species.…”
Section: Resultsmentioning
confidence: 99%
“…In plant pathology, Ag-NPs demonstrated antifungal and antiviral activity, as well as considerable nematicidal activity [ 28 , 29 ], improving plant growth indices and fruit output [ 30 ]. The application of Ag-NPs improved plant tolerance to a variety of biotic stressors, including phytopathogenic fungi [ 26 , 31 ] and worms [ 19 , 28 ]. Their application to plant viral diseases, however, is relatively limited [ 17 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles may be classified into organic and inorganic varieties [3][4][5][6]. Throughout the globe, inorganic nanoparticles have been used in nanomedicine, medication delivery, cosmetics, electronics, and the energy sector [7,8]. Among metal nanoparticles, silver nanoparticles (Ag NPs) have received attention not only in the researches field.…”
Section: Introductionmentioning
confidence: 99%